Systems and Computer Technology : proceedings of the 2014 International Symposium and Computer Technology (ISSCT 2014), Shanghai, China, 15-17 November 2014 /: proceedings of the 2014 International Symposium and Computer Technology (ISSCT 2014), Shanghai, China, 15-17 November 2014. (2015) - Unknown
No abstract available